2011
DOI: 10.1080/13537113.2011.622651
|View full text |Cite
|
Sign up to set email alerts
|

Culture vs. Rational Choice: Assessing the Causes of Religious Discrimination in Muslim States

Abstract: This study focuses on explaining the variation in the treatment of religious minorities in Muslim-majority countries using a novel dataset on religious discrimination-the Religion and StateMinorities (RASM) Dataset. As few theories exist to explain the causes of religious discrimination, this study compares theories related to general religion-state relations based on ideology, culture, and rational choice. We find that while political and structural factors are important in explaining variation in levels of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Aiming to explain variation in the treatment of religious minorities across Muslimmajority countries, Sarkissian et al (2011) show that factors unique to how countries' religious marketplaces are regulated play a significant role in predicting discrimination.…”
Section: The Literature On Religious Minority Discriminationmentioning
confidence: 99%
“…Aiming to explain variation in the treatment of religious minorities across Muslimmajority countries, Sarkissian et al (2011) show that factors unique to how countries' religious marketplaces are regulated play a significant role in predicting discrimination.…”
Section: The Literature On Religious Minority Discriminationmentioning
confidence: 99%
“…Uncovering these sources is important for many reasons, but the most significant is that denying religious freedoms has powerful political and social consequences. A series of recent studies, often using the new data, have found that restricting religious freedoms is associated with higher levels of physical persecution and open discrimination against religions (Akbaba and Fox ; Fox ; Grim and Finke ; Sarkissian, Fox, and Akbaba ) and an increase in religiously motivated violence (Akbaba and Taydas ; Finke and Harris ; Finke and Martin ; Henne ; Philpott ; Toft, Philpott, and Shah ). When seeking to understand the decline of liberal nationalism and the rise of fundamentalism in Egypt, Syria, Iran, and Algeria, Mansoor Moaddel () stressed the importance of allowing religions to enter into the public discourse and the cultural conversations.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, regulation is expected to be more effective in giving rise to gender equality in states where the religion is more patriarchal (H5). Studies suggest that Islam may be more patriarchal than other religions (Casanova, 2009;Sarkissian et al, 2011), and that Muslims hold more conservative views on gender relations (Inglehart and Norris, 2003). 5 Finally, religious states tend to be more sacralized (Stark and Finke, 2000), and this is another way in which a country's culture can become highly patriarchal.…”
Section: Boundary Conditions On the Effect Of Religious Regulationmentioning
confidence: 99%